SPEECH FUNCTIONS IN THE ELLEN DEGENERES’ SHOW - Aprilia, Helena (Sanata Dharma University, Yogyakarta, 2022)
Learning and having a deep understanding of speech functions are important in order to diminish misunderstanding in a process of communication. Thereupon, this research aims to identify the speech functions used by Ellen DeGeneres and her guests. In this research, the researcher formulated two research questions: 1) Which speech functions that are used by Ellen DeGeneres and her guests? and 2) What are the differences of speech functions used by Ellen DeGeneres and her guests? In order to answer the research questions, the researcher used the qualitative data method by applying content analysis. There are then found six speech function categories used by Ellen DeGeneres. Those functions were instrumental, regulatory, representational, interactional, personal, and heuristic. Moreover, Ellen’s guests used five speech functions. Those functions were regulatory, representational, interactional, personal, and heuristic. In the five videos, Ellen was more dominant in using heuristic and regulatory functions. Meanwhile, Ellen’s guests were more dominant in using interactional, regulatory, and representational functions.